2023
DOI: 10.1021/jacs.3c01317
|View full text |Cite
|
Sign up to set email alerts
|

Selective Cleavage of Chemical Bonds in Targeted Intermediates for Highly Selective Photooxidation of Methane to Methanol

Abstract: Restrained by the uncontrollable cleavage process of chemical bonds in methane molecules and corresponding formed intermediates, the target product in the reaction of methane selective oxidation to methanol would suffer from an inevitable overoxidation process, which is considered to be one of the most challenging issues in the field of catalysis. Herein, we report a conceptually different method for modulating the conversion pathway of methane through the selective cleavage of chemical bonds in the key interm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…In contrast, for the Yeager‐type O 2 adsorption on ZIS, there's a discernible endergonic challenge when it comes to activating oxygen molecules. The Pauling‐type adsorption of O 2 on P 2 ZIS appears primed for *OOH generation, attributable to the more facile energy barriers (0.11 eV) as opposed to the Yeager‐type configuration observed in ZIS (0.30 eV) [28] . This underscores the role of P atoms neighboring Zn active sites in transmuting the O 2 adsorption configuration from Yeager‐type to Pauling‐type.…”
Section: Figurementioning
confidence: 89%
See 1 more Smart Citation
“…In contrast, for the Yeager‐type O 2 adsorption on ZIS, there's a discernible endergonic challenge when it comes to activating oxygen molecules. The Pauling‐type adsorption of O 2 on P 2 ZIS appears primed for *OOH generation, attributable to the more facile energy barriers (0.11 eV) as opposed to the Yeager‐type configuration observed in ZIS (0.30 eV) [28] . This underscores the role of P atoms neighboring Zn active sites in transmuting the O 2 adsorption configuration from Yeager‐type to Pauling‐type.…”
Section: Figurementioning
confidence: 89%
“…The Pauling-type adsorption of O 2 on P 2 ZIS appears primed for *OOH generation, attributable to the more facile energy barriers (0.11 eV) as opposed to the Yeager-type configuration observed in ZIS (0.30 eV). [28] This underscores the role of P atoms neighboring Zn active sites in transmuting the O 2 adsorption configuration from Yeager-type to Pauling-type. Furthermore, these proximal P atoms around Zn active sites are theoretically adept at stabilizing the ratelimiting *OOH intermediates (while ZIS exhibits a tendency for oxygen-oxygen bond cleavage), thus affording a strategic advantage in modulating the selectivity and activity of H 2 O 2 in P 2 ZIS.…”
Section: Methodsmentioning
confidence: 94%
“…To verify the effect of the reaction pathways in the change of the CH 4 photooxidation performance, Zhou et al used the in-situ DRIFTS measurement to dynamically monitor the effect of different metal oxides on CH 4 photooxidation into CH 3 OH (Figure 21). [61] It is indicated that there are overoxidation products involving HCHO and CO 2 generated on the ZnO surface during the reaction process, no visible adsorption band assigned to CH 2 * detected on the P25 surface, but several adsorption bands assigned to the overoxidation product appear. Different from them, on Ga 2 O 3 only CH 3 O* intermediates are detected.…”
Section: Redox Mechanism Analysismentioning
confidence: 95%
“…Three key peaks were investigated: lattice oxygen (∼530.13 eV, bulk lattice oxygen is also involved), oxygen near the oxygen vacancies (∼531.30 eV), and hydroxyl groups or surface-adsorbed oxygen (∼532.30 eV). 37,44,45 It can be seen that Au modification measurably increased surface O v , which favors the activation of O 2 and the turnover of oxygen species through a reported evolutionary pathway of oxygen: 8,23,37,46 The existence of surface O v provided sites for the activation of O 2 , and as a result, more O 2− could be generated from O 2 and facilitate selective C−H activation upon photoexcitation.…”
mentioning
confidence: 99%
“…This is further corroborated by theoretical calculations indicating a substantial decrease in the energy required for O v formation at interface sites in the presence of Au due to the effects of lower valence dopants, such as Au. , To further test this understanding, we next performed X-ray photoelectron spectroscopy (XPS, Figure c). Three key peaks were investigated: lattice oxygen (∼530.13 eV, bulk lattice oxygen is also involved), oxygen near the oxygen vacancies (∼531.30 eV), and hydroxyl groups or surface-adsorbed oxygen (∼532.30 eV). ,, It can be seen that Au modification measurably increased surface O v , which favors the activation of O 2 and the turnover of oxygen species through a reported evolutionary pathway of oxygen: O 2 ↔ O 2 – ↔ O 2 2– ↔ 2O – ↔ 2O 2– (surface lattice). ,,, The existence of surface O v provided sites for the activation of O 2 , and as a result, more O 2– could be generated from O 2 and facilitate selective C–H activation upon photoexcitation.…”
mentioning
confidence: 99%